O judiciário e a possibilidade de solver conflitos políticos - Santos, Rodolpho Oliveira (2022)
The present research investigates the possibilities of an analysis by the judiciary of conflicts arising from the political system and how such analysis takes place. The problematic of the use of multifunctional dialectics and the limitations of the legal system in interfering in the political system and vice-versa, those questions are the object of the analysis. The work seeks to key the assumptions for such an analysis and goes through discussions on dialectics, language, systems’ theory, political science, separation of powers theory, and grounds for deciding. The research involved the analysis of historical texts, the main theories on the theme, the evolution and gain of legitimacy of the judiciary in Brazil and some paradigm countries that are fundamental to our system. The work reviews the factual condition of the courts' handling of conflicts arising from politics and verifies that this has been occurring in practice, as well as verifies the stretches marks of such performance and suggests a procedural approach to conflicts and decision making, with emphasis on the performance of the Supreme Court